PERANCANGAN SISTEM INSTRUMENTASI BERBASIS INTERNET OF THINGS PADA MODERN AGRICULTURE - Sulistio Nanda Reynara; Ulinnuha Latifa; Lela Nurpulaela (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2023)
Indonesians depend on the agricultural sector as a source of daily livelihood.With rice as the staple food of Indonesian people, it is no stranger to the term seeding.The seeding process is the process of growing seeds until they become seedlings that are ready for planting.The importance of the seeding process is because, the seeding process serves to reduce the mortality that occurs in seeds.The superior quality of seedlings is influenced by several factors during the seeding process, namely: soil moisture, room temperature, room humidity and water pH.To maintain the optimality of the seeding process, it is carried out by monitoring these factors using 3 sensors, namely: the YL-69 sensor to monitor soil moisture, the DHT-11 sensor to monitor room temperature and room humidity, and the SEN0161 pH Meter sensor to monitor the pH of water.All three sensors are controlled by the NodeMCU ESP32 microcontroller to process the data.The level of accuracy is generated through comparison of sensors and conventional measurements. An accuracy of 99.16% for temperature and 99.66% for room humidity, while an accuracy value accuracy of 100% is produced on soil moisture and water pH. By monitoring these factors in the seeding process, the seeding can take place optimally and get superior seedling yields.